Main legal risks in provision of commercial medical services by state medical institution - E. V. Pesennikova; O. V. Gridnev; S. A. Korostelev (Исследования и практика в медицине)
Based on the analyses of normative-legislative documents related to medical activities in RF published between 1990 and 2017 the classification of medical facility legal risks has been formed. The usage of the classification enables building systematic approach for legal protection.The right for health protection is ensured also by providing paid medical services according to the Federal Act on Public Health Care. It doesn’t follow from Russian legislation that this right could be exercised only in private medical institutions, which makes public medical institutions legitimate participants of the process. However, in accordance with the Government Resolution No. 1006, there is range of restrictions for public medical institutions in case they provide paid medical services. For instance, they must justify charging by informing consumers about their rights guaranteed by the State guarantees program.The analysis of normative-legislative documents that ensure regulation of public medical services caused the classification of legal risks. The violation of the Consumer Protection Act and of the Civil Code (contractual risks) appeared to become the most common ones.There is no clear notion of “medical error”. That’s why it is almost impossible to make a distinction between patient irresponsibility, staﬀ negligence or low doctor’s professionalism. This is the reason for patients’ rights as well as medical personnel responsibility to be regulated by the state.The analysis that is been made shows that risks and sanctions in the provision of Paid Medical Services by State institutions occur in cases of misconduct while providing Paid Medical Services. The most typical cases of misconduct while providing Paid Medical Services come when: medical services could be provided under the State guarantees program; failure to provide medical care occurs; violation of medical and contractual documents in the provision of Paid Medical Services takes place; violation of patient’s rights to receive complete and reliable information related to medical care takes place.